Implementation of AHP and WASPAS (Weighted Aggregated Sum Product Assessment) Methods in Ranking Teacher Performance - Mesran Mesran; Suginam Suginam; Dito Putro Utomo (IJISTECH (International Journal of Information System and Technology), 2020)
The performance of a teacher is an outcome that is demanded by the School Principal in awarding a teacher who is at a formal level of education. In producing effective decisions on performance ratings, it is, of course, necessary to use a computer-based information system, this is known as the Decision Support System. In order for the resulting decisions to be better, using methods that can process existing data so that the method used is able to produce a final report in the form of a decision. At SD IT Al-Munadi Marelan-Medan, so far not using computer applications to help decision-makers to rank teacher performance. Although all this time the needs of the school principal are reports on the performance of teachers in schools. In the research that the authors conducted using a combination of AHP and WASPAS methods which are expected to improve the results of decisions on teacher performance ranking.